Is There A Future After The Belo Monte Dam? Building Futures Scenarios For The Volta Grande Do Xingu In Amazonia, Brazil - Ferreira-Aulu, Marianna (fi=Turun yliopisto|en=University of Turku|, 2017)
The Belo Monte Dam is being built in Amazonia, Northern Brazil, and once completed, it will be one of the four largest hydroelectric power plants in the world. The power plant is a major infrastructure project in Brazil that should contribute to the country’s energy security and benefit the economy. As any large construction, it also has potential drawbacks. Due to its location, Belo Monte already have and will continue to disrupt ecossystems and human lives. The negative impacts of the dam have created polemic discussions among different interest groups. This controversy is investigated in this paper in its various aspects: political, ecological, cultural, social, and economic. The findings of this research are presented in the form of scenarios of alternative future possibilities for the region. This Master’s Thesis aims at helping different interest groups to envision alternative futures with these scenarios, and to provide tools to create change towards their preferred futures.